RELATIONSHIP BETWEEN FAMILY SUPPORT WITH LOW-SALT COMPLIANCE IN ELDERLY HYPERTENSION AT SEI MENCIRIM HEALTH CENTER: Hubungan Dukungan Keluarga dengan Kepatuhan Diet Rendah Garam Pada Lansia Hipertensi Di Puskesmas Sei Mencirim - Edy Samosir Pakpahan, Jun; Pujiati, Lilis (Jurnal Berkala Epidemiologi, 2024)
Background: Hypertension is a chronic health condition that cannot be cured. It is caused by high sodium consumption, obesity, stress, smoking, and alcohol consumption. Purpose: Determine the relationship between family support and adherence to a low-salt diet in the working area of ​​the Sei Mencirim Health Center, Deli Serdang District, for the elderly with hypertension. Methods: The population in this study was older adults with hypertension, totaling 110 respondents. The sample in this study was 52 respondents using a purposive sampling technique, using univariate and bivariate data analysis with the chi-square test. Results: The results of the chi-square statistical test obtained a p-value of 0.00 compared to the value of α = 0.05, so the p-value < 0.05 (0.00< 0.05). This means that there is a significant relationship between family support and adherence to a low-salt diet in the elderly with hypertension in the Sei Mencirim Health Center, Deli Serdang District. Conclusion: This study found that there is a significant relationship between family support and adherence to a low-salt diet in the elderly with hypertension. It is hoped that health workers will provide more information about adherence to a low-salt diet in hypertensive patients through health education.